Hubungan Anxiety Disorders dengan Kesulitan Tidur pada Remaja di Bukittinggi - Asri Rima Oktavia; Miksa Denola Dusatri; Tesa Anggraini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The phenomenon of sleep difficulties is currently a major problem in adolescents. Several epidemiological studies have investigated the relationship between theoccurrence of sleep disturbances and anxiety disorders in the general population. This research was conducted with the aim of finding a significant positive relationship between sleep difficulties and anxiety disorders. The research method uses quantitative research with data analysis techniques using Pearson's Correlation and linearity assumption tests. The population in this study were teenagers in the Bukittinggi area with a total sample of 106 teenagers. The results of the linearity test showed a significant value of p > 0.05 and the resulting Pearson's r value was 0.532. The results of the analyses show that there is a significant positive relationship between anxiety disorders and difficulty sleeping, so that the hypothesis in this study can be stated as accepted.